2020
DOI: 10.1088/1742-6596/1529/3/032006
|View full text |Cite
|
Sign up to set email alerts
|

Tricet Method to Increase the Hypertrophy Muscle

Abstract: Tricet method of weight training is an exercise that involves using three types of tools to train one group muscle in the sequence order, but with different types of exercises for each set and without breaks between sets. Exercise with this method is able to provide maximum response to a group of muscles that are trained so that the potential for muscle development is more optimal. This paper investigates this method by giving a treatment in the form of weight training with the tricet method to be carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Weight training is done using your weight (internal weight) or using external weights such as dumbbells, barbells, and machines. (Nasrulloh et al, 2020). As a study found that there was a significant effect of bodyweight training with total-body resistance exercise (TRX) on increasing muscle strength which included increasing leg muscle strength, back muscle strength, hand muscle strength, arm muscle pulling strength, and pushing muscle strength.…”
Section: Resultsmentioning
confidence: 99%
“…Weight training is done using your weight (internal weight) or using external weights such as dumbbells, barbells, and machines. (Nasrulloh et al, 2020). As a study found that there was a significant effect of bodyweight training with total-body resistance exercise (TRX) on increasing muscle strength which included increasing leg muscle strength, back muscle strength, hand muscle strength, arm muscle pulling strength, and pushing muscle strength.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term athlete development (LTAD) theory states that athlete ages ranged from 19-23. The purpose of training is to maximize and integrate mental, cognitive, and physical development [24] [63]. In another literature, it is stated that ages 19 and over aim to develop further in terms of technique, strategy as well as improve and maintain the physical component [24].…”
Section: Discussionmentioning
confidence: 99%
“…A person with good physical fitness will be able to carry out daily activities relatively longer when compared to someone who has a low level of physical fitness (Nasrulloh et al, 2020;Nugroho et al, 2021). Physical fitness is very important for someone, so everything that supports a good level of physical fitness, is strived to be applied since early childhood.…”
Section: Introductionmentioning
confidence: 99%